Pemberdayaan Petani Komoditi Dalam Meningkatkan Pendapatan Masyarakat Di Kecamatan Nangapanda Kabupaten Ende - Sayful Amrin (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
The aims of study to find determine the commodity in the empowerment of farmers increase incomes in village Ndetuzea Subdistricts Nangapanda Ende Region. Research district is using a qualitative approach through interviews, observation and documentation. The proves that empower farmers increase incomes commodity in the village of Ndetuzea can help provide insight to the public about the importance of agricultural extension programs thus contributing to the increase in income community.